Pneumatosis cystoides intestinalis mimicking acute abdomen - Kaya, Bülent; Çelik, Kafkas; Karip, Aziz Bora; Altun, Hasan; Özbay Özel, Nurver; Bat, Orhan; Memişoğlu, Kemal (Turkish Journal of Gastroenterology, 2014)
Abstract Pneumatosis cystoides intestinalis (PCI) is a rare disease. It was first described by Du Vernoy in 1793 during a cadaver dissection. Air-filled bubble-like lesions are located in the submucosa or the subserosa of the digestive tract. A 55-year-old Turkish male presented to the emergency department with complaints of recurrent abdominal pain and vomiting. Free air was detected in abdominal x-ray and abdominal computed tomography (CT). In exploration, a grape-like lesion consisting of hundreds of cysts was detected on the surface of the small intestine. Bowel resection was performed successfully. The surgical findings and pathological result confirmed the diagnosis of pneumatosis cystoides intestinalis.